Pengaruh ekstrak daun rambutan (Nephelium lappaceum L.) terhadap kematian larva nyamuk aedes aegypti - Fajriansyah Fajriansyah (Politeknik Kesehatan Kemenkes Aceh, 2019)
Background: The effort to control mosquitoes can be done by terminating the life cycle of mosquitoes, eradication of the larval sadium, namely larvicides. Rambutan leaves (Nephelium lappaceum L.) contain tannin compounds, saponins. Saponins are destroying red blood cells through the reaction of hemolysin, are toxic to cold-blooded animals, including cold-blooded insects, one of the insects that often interfere with human life is mosquitoes.Objectives: The purpose of this study was to determine the extract of rambutan leaves on the death of Aedes aegypti larvae Methods: This research is an experimental research. The object of research was Aedes aegypti mosquito larvae. The study was conducted at the writer home of Lamjamee Village, Banda Aceh. Research time is August 23-25, 2017. Type of research is an experimental study that is the effect of rambutan leaf extract on the death of Aedes aegypti larvae. The object of research is the population of Aedes aegypti larvae. The research subjects taken were Aedes aegypti mosquito larvae that lived because of the administration of rambutan leaf extract with a concentration of 5%, 10%, 15%. Statistical data analysis used Anova LSD test.Results: The results showed that the death of Aedes aegypti larvae by using rambutan leaf extract (Nephelium lappaceum L.) dose of 5% with an average of 19.7. Dose 10% had an average of 34.3, and a dose of 15% of the average mortality was 43.7. There is a significant difference between each dose of the mortality rate of Aedes aegypti larvae, with a value of F= 28.1 (F-count > F-table = 4.07).Conclusion: Various concentrations of the three treatments of rambutan leaf extract namely 5%, 10% and 15% are very effective against the death of Aedes aegypti larvae. Suggestions, can be used and practiced in everyday life, so as to reduce the use of chemical insecticides.